2023
DOI: 10.3390/diagnostics13040657
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Gallbladder Drainage versus Percutaneous Gallbladder Drainage for Acute Cholecystitis: A Systematic Review and Meta-Analysis

Abstract: Background: Percutaneous transhepatic gallbladder drainage (PT-GBD) has been the treatment of choice for acute cholecystitis patients who are not suitable for surgery. The effectiveness of endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) as an alternative to PT-GBD is not clear. In this meta-analysis, we have compared their efficacy and adverse events. Methods: We adhered to the PRISMA statement to conduct this meta-analysis. Online databases were searched for studies that compared EUS-GBD and PT-GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…This is similar with another study using the NIS database from 2005 to 2014, which showed that patients undergoing percutaneous drainage for acute cholecystitis were signi cantly older compared to those undergoing cholecystectomy or no intervention [29]. However, various meta-analyses analyzing different drainage modalities for cases of acute cholecystitis and malignant obstruction have shown no correlation with age [30,31].…”
Section: Discussionsupporting
confidence: 84%
“…This is similar with another study using the NIS database from 2005 to 2014, which showed that patients undergoing percutaneous drainage for acute cholecystitis were signi cantly older compared to those undergoing cholecystectomy or no intervention [29]. However, various meta-analyses analyzing different drainage modalities for cases of acute cholecystitis and malignant obstruction have shown no correlation with age [30,31].…”
Section: Discussionsupporting
confidence: 84%
“…In the recent meta-analysis, EUS-GBD procedure was compared with PT-GBD, where the pooled technical success was 89.9% [95% confidence interval (CI): 0.87-0.92] and 87.5% (95%CI: 0.85-0.90), respectively[ 16 ]. Clinical success in EUS-GBD group was observed in 97% (95%CI: 0.95-0.98) of patients, and in 94.1% (95%CI: 0.92-0.96) of the patients treated with PT-GBD[ 16 ].…”
Section: Acute Cholecystitismentioning
confidence: 99%
“…In the recent meta-analysis, EUS-GBD procedure was compared with PT-GBD, where the pooled technical success was 89.9% [95% confidence interval (CI): 0.87-0.92] and 87.5% (95%CI: 0.85-0.90), respectively[ 16 ]. Clinical success in EUS-GBD group was observed in 97% (95%CI: 0.95-0.98) of patients, and in 94.1% (95%CI: 0.92-0.96) of the patients treated with PT-GBD[ 16 ]. Despite that above mentioned results for AC treatment were almost comparable, differed significantly when AEs rate was assessed, ranging 14.6% and nearly 30% for EUS-GBD and PT-GBD, respectively.…”
Section: Acute Cholecystitismentioning
confidence: 99%
“…
Rescuing maldeployment of lumen-apposing metal stent for the management of acute cholecystitisEndoscopic ultrasound (EUS)-guided transmural drainage with a lumen-apposing metal stent (LAMS) has expanded its indications for off-label use including gallbladder drainage (GBD). [1][2][3][4] Maldeployment is one of the immediate complications. 1,5 Here we present a surgically unfit 85-year-old woman with acute cholecystitis (Fig.
…”
mentioning
confidence: 99%